Effect of passive smoking as a risk factor for chronic obstructive pulmonary disease in normal healthy women - Kalyan, Meenakshi; Kanitkar, Shubhangi A.; Gupta, Aayush; Sharma, Devanshi; Singh, Sanam (International Journal of Research in Medical Sciences, 2016)
Background: Environmental tobacco smoke (ETS) is a risk factor for cardiovascular disease, asthma in children and lung cancer. There is a biological plausibility of ETS as a causal factor for COPD. Objectives of the study were to examine the effect of passive smoking on lung function in non-smoking healthy women and to co-relate the effects of passive smoke as a risk factor for COPD. Methods: 50 women between 20-40 years of age exposed to passive smoke at home and workplace were assessed by questionnaire. The pulmonary function tests were performed and the values of FEV1 and FVC were obtained by a spirometer. Results: Out of 50 women, 34 % at workplace, 54% at home and 12% at home and workplace were exposed. Mean age was 30.3 years. Mean±SD of FEV1 was 1.94±0.9, FVC was 2.54±1.06, FEV1/FVC was 73.5±10.06 predicted FEV1 % was 63.2±23.2. FEV1/FVC of women exposed at home and workplace was 70.84 indicating that they have higher chances of developing COPD later in life. Conclusions: Passive smoking represents a serious health hazard that can be prevented by health education campaigns.